2011
DOI: 10.1097/bpo.0b013e31821a5e27
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Forearm Deformity by Distraction Osteogenesis in Children With Relative Shortening of the Ulna Due to Multiple Cartilaginous Exostosis

Abstract: In agreement with literature reports, carpal balance can be restored over the medium term. However, mild recurrences of ulnar shortening and radial malformation were observed during further development. To prevent deformity progression in immature patients, surgery should be carried out early. The optimal timing of surgery needs to be calculated precisely to take advantage of the high remodeling potential and an acceptable degree of recurrent deformity. Ulnar lengthening is necessary, but overcorrection is ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 0 publications
1
34
0
Order By: Relevance
“…2 Anatomic reduction and stable fixation of ulnar fractures, especially in Monteggia variants, are essential to ensure an accurate reduction of the radial head. [4][5][6][7] The findings in this study suggest that the AP ulnar proximal angle in skeletally immature children is smaller than in adults and is located relatively more distal. Therefore, knowing the parameters that define the normal ulna may help the treating surgeon in managing these pathologies.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…2 Anatomic reduction and stable fixation of ulnar fractures, especially in Monteggia variants, are essential to ensure an accurate reduction of the radial head. [4][5][6][7] The findings in this study suggest that the AP ulnar proximal angle in skeletally immature children is smaller than in adults and is located relatively more distal. Therefore, knowing the parameters that define the normal ulna may help the treating surgeon in managing these pathologies.…”
Section: Discussionmentioning
confidence: 58%
“…Monteggia fracture-dislocation of the proximal ulna and radius is rare (2% to 5% of elbow injuries) and extremely difficult to treat because only an anatomic reduction can restore joint congruence, fracture stabilization, and subsequent functional rehabilitation. [5][6][7] The adult ulna has been previously described in the literature in cadaveric studies with general consensus on the mean varus angulation of the proximal ulna (17.5, 17.7 degrees) and the mean distance from the triceps insertion to the ulnar proximal angulation point (8.54, 7.32, 7.6 cm). Similar upper limb deformities are also common in patients with osteogenesis imperfecta.…”
mentioning
confidence: 99%
“…Akita 10 reported similar phenomena in corrective surgery that initial improvement was lost after 13 years of follow-up. Analysis of the raw data in Vogt et al 12 and Tang et al 14 series showed that the final improvement in UV fell short of the initial ulnar lengthening in 71% of cases (Table 3). This rebound phenomenon is poorly understood.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, unlike one bone lengthening, the ulna cannot be lengthened to the anticipated length at one stage without considering the balance between the radius and ulna. In addition, some authors proposed that ulnar overlengthening could result in ulnocarpal impaction and should be not recommended even in patients with higher risk for recurrence [22,23].. In contrast, Hill et al, who mentioned that overcorrection was partially successful at preventing subluxation or dislocation of the radial head [24].…”
Section: Discussionmentioning
confidence: 99%